Ontology in Requirements Software Development Method: A Systematic Literature Review - Fauzan, Reza; Hamidi, Mohammad Zaenuddin; Safitri, Winda Ayu; Siahaan, Daniel Oranova; Karimi, Muhammad Ihsan (Department of Information Systems and Technology, Faculty of Intelligent Electrical and Informatics Technology, Universitas 17 Agustus 1945 Surabaya, 2025)
The requirement process is one of the most critical factors in determining whether the software development process is successful. It is crucial to consider the function that ontology plays in the requirements of software engineering development. People and organizations can more easily utilize and share data, information, and knowledge with one another because of the implementation of ontology. During our systematic assessment of the literature published between 2011 and 2020, we came across twenty publications that discussed ontology in requirements and how it might be used in software development processes. To determine which studies were the most pertinent to our research endeavors, we developed and implemented inclusion and exclusion criteria in two separate rounds. The review identified the leading ontology in data software development challenges. We found various ways to do this in our selected papers with different systematics as well. However, our findings indicate that the ontology requirements in software development must be addressed by examining various software development methods apart from agile scrum and XP.